The Relationship between Literacy Skills and Students' Academic Achievement: A Meta-Analysis Study - Kurniawati, Kurniawati (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2024)
Literacy skills and academic achievement were examined in this study. An individual's capacity to learn and apply new skills relies heavily on their ability to read and write well. In this study, a meta-analysis approach is used to calculate the correlation with the fixed-effect model, which is quantitative. The first step in formulating research questions is to identify relevant research and then look for research that doesn't publish the r-value. There are 29 articles in the sample. This study's findings on the relationship between literacy skills and student academic achievement are free from publication bias because the fixed-effect funnel plot model shows a variety of sample sizes with the asymmetric distribution. After seeing the forest plot before and after trimming and filling it, it was clear that the results of the summary effect were evident. So, the fixed-effect model of the relationship between students' reading skills and how well they do in school is very likely to be true.